Impact of wastewater irrigation on vegetative growth, flowering characteristics, keeping quality and productivity of tuberose (Polianthes tuberosa) - GURJAR, D S; KAUR, R; SINGH, K P (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted to assess the impact of wastewater irrigation on vegetative growth, flowering characteristics, keeping quality and productivity of tuberose (Polianthes tuberosa L. cv. Prajwal) at WTC farm of ICAR-Indian Agricultural Research Institute, New Delhi during three consecutive seasons of the year 2013-14, 2014-15 and 2015-16. Seven treatments were taken as T-1: Wastewater irrigation at 0.6 irrigation depth (ID)/ cumulative pan evaporation (CPE), T-2: Wastewater irrigation at 0.8 ID/CPE, T-3: Wastewater irrigation at 1.0 ID/CPE, T-4: Wastewater irrigation at 1.2 ID/CPE, T-5: Wastewater irrigation at 1.4 ID/CPE, T-6: Conjunctive use of groundwater and wastewater irrigation at 1.0 ID/CPE in cyclic mode, T-7: Control (groundwater irrigation at 1.0 ID/CPE) in randomized block design with three replications. Results indicated that the vegetative growth parameters such as days to sprouting of bulb, days to spike emergence, number of leaves/clump, length and width were not much changed, whereas the significantly higher values of flowering parameters such as spike length, rachis length and number of florets/spike were observed under application of wastewater irrigations at 1.2 ID/CPE. Keeping quality parameters such as durability of spike and flower in field and vase life of spike and flower were not significantly affected due to application of wastewater irrigations in tuberose. Significantly higher marketable cut spike and loose flower yield was observed where wastewater irrigations applied at 1.2 ID/CPE. It is concluded that wastewater irrigation is suitable for enhancing the productivity of tuberose without deteriorating the keeping quality of tuberose flowers.